Relative positional change of a dental implant in the esthetic zone after 12 years: A case report - Jardini, Maria Aparecida Neves [UNESP]; Ferreira, Camila Lopes [UNESP]; Ursi, Weber José; De Melo Filho, Antonio Braulino; Santamaria, Mauro Pedrine [UNESP] (My University, 2017)
Although the biological process of osseointegration is similar in adults and adolescents, implant placement is contraindicated in young patients until bone growth is complete. However, even in adults, significant craniofacial changes may occur over an individual's lifetime, as a result of discrete and continuous dental eruption, vertical soft tissue augmentation, or facial bone growth. After such changes, implants may be in infraocclusion. The present case report describes the long-term follow-up of a dental implant located in the esthetic zone. The implant, placed when the patient was 20 years old, demonstrated a relative positional change 12 years postinsertion. The possible reasons for the movement and the long-term clinical implications of this type of case are discussed.
Keywords: Esthetics; Implants; Positional change